Physical activity level in Physical Therapy students - Martins, J. (2021)
Physical activity is defined as any body movement that requests energy expenditure. The practice of physical activity allows to reinforce and increase the capacity of muscular-skeletal response and an improvement of physical aptitude. Currently, has been verified that university students have been decreasing healthy lifestyles and increasing their degree of sedentary lifestyle. Thus, it’s essential the Higher Education Institutions present themselves as a way to promote the practice of physical activity and contemplating it in the basic formation.